Experimental Investigation of Steel Corrosion in Concrete Structures by Acoustic Emission Analysis - Elfergani, Hisham A. (Scientific Journal of University of Benghazi, 2024)
Corrosion represents a significant issue in various structures, with reinforced and prestressed concrete particularly susceptible. In certain applications, it demands specific attention and mitigation strategies, special attention must be paid to ensure that failure does not occur, as it could lead to loss of life and incur significant financial expenses. This paper examines the role of Acoustic Emission (AE) as a non-destructive testing (NDT) technique for reinforced concrete structures. The work focuses on the development of experimental techniques and data analysis methods for the detection, location, and assessment of AE from reinforced concrete specimens due to steel wire corrosion. The results reveal that AE can be used to detect the onset of corrosion activity in wire in the interface between prestressed concrete and mortar as found in prestressed concrete pipes. It has been shown that by using AE and the relationship between RA and AF value, the crack area can be located and identified. Hence, it could be possible to provide a corrosion alarm and location prior to any wire breaks. Furthermore, the results offer encouragement for the use of the AE technique to detect early corrosion and macro cracks in large concrete pipe structures.